2007
DOI: 10.1111/j.1447-0756.2007.00663.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human papillomavirus DNA and genotyping in patients with epithelial ovarian carcinoma

Abstract: HPV may have a role in the carcinogenesis of ovarian cancer. It is worth investigating this possible relation both in large case-control studies and in vitro models by using more sensitive techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 21 publications
3
28
0
3
Order By: Relevance
“…This finding was in agreement with other study found that the presence of high-risk types of HPV was found in the serous histological subtype and advanced stages of the disease (FIGO stages III and IV) [39]. Other studies showed no evidence of high-risk HPV association with histological subtype and/or stage of disease [4,24].…”
Section: Discussionsupporting
confidence: 93%
“…This finding was in agreement with other study found that the presence of high-risk types of HPV was found in the serous histological subtype and advanced stages of the disease (FIGO stages III and IV) [39]. Other studies showed no evidence of high-risk HPV association with histological subtype and/or stage of disease [4,24].…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have demonstrated an association of HPV with ovarian cancers [2, 3, 51]. We detected molecular signatures of high risk HPV16 and 18 along with other low risk HPVs in the ovarian cancer samples screened.…”
Section: Discussionmentioning
confidence: 93%
“…The etiology of OCa is multifactorial; the main causes are genetic, environmental, and sexual behavior and HPV which is the main pathogen that leads to OCa (21). Previous studies report different ranges of HPV prevalence in OCa, even some studies were unable to detect HPV in OCa (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…So, previous studies have documented the increase of HPV-16 associated OCa in Iran. Atalay (2007) in Turkey reported 8.5 % HPV in OCa patients (21). Rosa et al (2013) in a meta-analysis study showed a range of 0% to 66.7% HPV prevalence with a mean of 17.5% in OCa patients and, more, reported the highest HPV prevalence in Asia at 31.4%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation